Risk Factor Assessments and Lipid Management Patterns in Hospitalised Patients in Malaysia: The Atherosclerotic Cardiovascular Disease Study - Rosman, Azhari; Looi, Zhi Ling; Fegade, Mayuresh; Thum, Chan Ho (Malaysian Journal of Medical Sciences, 2025)
Background: Elevated levels of low-density lipoprotein cholesterol (LDL-C) result in dyslipidaemia, increasing the risk of atherosclerotic cardiovascular disease (ASCVD). As of 2022, Malaysian population (56.7%) demonstrated high LDL-C, necessitating an analysis of cardiovascular risk factors (CVRFs), comorbidities and treatment using lipid-lowering therapies (LLTs) to achieve target LDL-C < 1.4 mmol/L, as per Malaysian guidelines. Methods: This retrospective cohort study of 431 hospitalised patients (? 18 years) with elevated LDL-C levels from the National Heart Institute, Malaysia, assessed CVRFs, comorbidities, treatment patterns, and the proportion of patients achieving LDL-C goals (< 1.8 mmol/L, < 1.4 mmol/L, and < 1.0 mmol/L) after LLT. The association pattern of CVRFs was studied in patients achieving the target goal of < 1.4 mmol/L. Results: The mean age of the patients was 60.53 (9.86) years, with the majority being male (79.35%), non-smokers (84.78%), and Malay (61.48%). Most patients (88.40%) had acute coronary syndrome, and the most prevalent risk factors were systemic hypertension (76.33%), diabetes mellitus (DM) (51.97%), and chronic kidney disease (CKD) (28.54%). Monotherapy with high-intensity statins was the most common LLT. At 1 year, 48.26%, 24.83% and 7.66% of patients had achieved target goals of < 1.8 mmol/L, < 1.4 mmol/L, and < 1.0 mmol/L, respectively. Poor LDL-C achievement was observed among patients with DM and recurrent events (P = 0.0097), left ventricular ejection fraction < 35% (P = 0.0325), and age > 75 years (P = 0.0087). Conclusion: Hypertension, diabetes and CKD are prevalent risk factors, and despite high-intensity statins, only 24.83% of patients achieved the LDL-C target goal. Thus, the use of combination therapy and innovative therapies is necessary to improve ASCVD management in Malaysia.